Bacteriophage ecology of fermented foods: anything new under the sun?. (August 2021) - Paillet, Thomas; Dugat-Bony, Eric
Graphical abstract: Highlights: Food fermentations are driven by microbial communities. Bacteriophages have an impact on the dynamics of food microbial communities. The precise roles of bacteriophages in fermented foods remain to be characterized. Abstract : Bacteriophage ecology has raised an increasing attention over the past few years, thanks to the improvement and contributions of microscopy, comparative genomics and viral metagenomics methods. Fermented foods host dense and diverse microbial communities and, therefore, represent an ideal biotope for bacteriophages. If their occurrence in such environments has been demonstrated decades ago, data highlighting their impact on mixed communities and their ecological roles are scarce when compared to other microbial ecosystems. This review summarizes most recent knowledge into the bacteriophage diversity of fermented foods and stress evidences suggesting the impact of these entities on the dynamics of food microbial communities. The main ecological roles played by bacteriophages in microbial ecosystems are also addressed. Understanding the impact of bacteriophages in fermented foods will further help in designing adapted microbial consortia and thus providing a better control of the food fermentations.